NUGGET AYAM DAN HALILING UNTUK MENCEGAH ANEMIA PADA BALITA: UJI KADAR PROTEIN, ZAT BESI, DAN TINGKAT KESUKAAN - Rizka Pramudyaningtyas; Nurul Hekmah; Sigit Yudistira; Nany Suryani (GIZI INDONESIA, 2022)
Toddlers are a group that is prone to anemia. One of the efforts to prevent anemia in a toddler is by fulfilling nutrients such as protein and iron. Chicken and haliling are high protein and iron foods that can be used to prevent anemia in toddlers. This study aims to determine the level of protein, iron and hedonic scaling (color, aroma, texture, and taste) of chicken nuggets and haliling as a snack for a toddler to prevent anemia. The method used in this study was a pure experimental design with a completely randomized design (CRD) with 4 treatments and 3 replications with the proportions of chicken and haliling P0 (100%:0%), P1 (90%:10%), P2 (80%:20%), P3 (70%:30%). The research panelists consisted of 25 untrained panelists. Analysis of protein content using the Kjeldahl method and iron using the visible spectrophotometric method, analysis of protein content data using Kruskal Wallis, iron using One Way Anova and hedonic scaling using Friedman. The results showed that there was an effect of the proportion of chicken and haliling on protein content (p=0.016), iron (p=0.001), color hedonic scaling (p=0.004), aroma (p=0.001), texture (p=0.001) and taste (p=0.001) on nuggets. The highest protein content at P3 was 11.27 g/100 g, the highest iron content at P3 was 2.2 mg/100 g, and the hedonic scaling for nuggets containing the proportions of chicken and halilings for color, aroma, texture, and taste was highest at P1 with an average of 3.2, 2.95, 3.25 and 2.85